2011
DOI: 10.1007/s11270-011-0944-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Toxic Effects of Nickel, Cadmium and EDTA on Growth of the Plant Growth-Promoting Rhizobacterium Pseudomonas brassicacearum

Abstract: Plant growth-promoting rhizobacteria (PGPR) play an important role in the biodegradation of natural and xenobiotic organic compounds in soil. They can also alter heavy metal bioavailability and contribute to phytoremediation in the presence or absence of synthetic metal chelating agents. In this study, the inhibitory effect of Cd 2+ and Ni 2+ at different concentrations of Ca 2+ and Mg 2+ , and the influence of the widely used chelator EDTA on growth of the PGPR Pseudomonas brassicacearum in a mineral salt med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Recently, the effects of Cd on microbial communities, such as the decrease of microbial taxonomic species and the change of microbial compositions in soil have received research attention ( Vig et al, 2003 ; Krujatz et al, 2012 ; Feng et al, 2018b ). Luo et al (2018) reported that high Cd level of agricultural paddy soil displayed lower bacterial community diversity than low Cd level sites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of Cd on microbial communities, such as the decrease of microbial taxonomic species and the change of microbial compositions in soil have received research attention ( Vig et al, 2003 ; Krujatz et al, 2012 ; Feng et al, 2018b ). Luo et al (2018) reported that high Cd level of agricultural paddy soil displayed lower bacterial community diversity than low Cd level sites.…”
Section: Introductionmentioning
confidence: 99%
“…When the content of PTEs increases in soil, especially in the rhizosphere zone, it causes changes in microbial activities and their composition. This could lead to poor nodulation in the legumes and inefficient root growth in cereals resulting in reduced nutrient translocation and absorption . As a result of poor nodulation in the legumes and imbalance of nutrients in the rhizosphere, the health of leguminous plants like green gram, pea, lentil, chickpea, and cereals such as rice, wheat, and maize, is adversely affected while grown on PTEs contaminated soils .…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, where chemical amendments using chelating agents are conducted to phytoextract Cd from soil ( Lambrechts et al, 2011 ), at the same time, these chemical amendments have a limitation of stunted plant growth, e.g., Pseudomonas brassicacearum ( Krujatz, 2012 ), Lolium perenne , Brassica juncea , and Typha angustifolia ( Muhammad et al, 2009 ; Goel and Gautam, 2010 ; Xu et al, 2010 ). Under such circumstances where the application of a single chelating agent resulted in stunted growth, application of a quick biodegradable chelate complex is a potential option for enhancing Cd phytoextraction ( Wang et al, 2019 ).…”
Section: Remediation Of Cadmium-polluted Soilsmentioning
confidence: 99%